Effect of AgNO₃ concentration in the preparation of hybrid Ag/TiO₂ and its photocatalytic activity: article - Zulpakar, Any Mastura; Lim, Ying Pei; Lim, Ying Chin (2017)
Hybrid of Ag/TiO₂ was successfully prepared by liquid impregnation process using Sliver Nitrate (AgNO₃) and Titanium Dioxide (TiO₂). Five hybrid of Ag/TiO₂ with difference in weight percent was prepared which are Bare TiO₂, 5 wt%, 10 wt%, 15 wt% and 20 wt%. The photocatalytic activity also studied to find the optimum concentration of the hybrid of Ag/TiO₂ using Methyl Orange (MO) as a model for waste water in the research. As a result, the optimum concentration was found to be at 5 wt% with percent of degradation is at 68.22. Structural and morphological characterizations have been accomplished through X-Ray powder diffractometry (XRD), EDX, and scanning electron microscopy (SEM). Characterization by using XRD spotted the existence of Ag element in samples. Hence, for further confirmation, EDX characterization also done which revealed the existence of Ag element in samples. SEM characterization indicates that no significant difference in morphology characteristics between Bare TiO₂ and after hybridization. The elaboration of this observation is described in detail in this paper.